Pressure and flow properties of dual-lumen cannulae for extracorporeal membrane oxygenation. (November 2020) - Broman, Lars Mikael; Westlund, C Jerker; Gilbers, Martijn; Perry da Câmara, Luisa; Prahl Wittberg, Lisa; Taccone, Fabio Silvio; Malfertheiner, Maximilian V; Di Nardo, Matteo; Swol, Justyna; Vercaemst, Leen; Barrett, Nicholas A; Pappalardo, Federico; et al.
Introduction: In the last decade, dual-lumen cannulae have been increasingly applied in patients undergoing extracorporeal life support. Well-performing vascular access is crucial for efficient extracorporeal membrane oxygenation support; thus, guidance for proper cannulae size is required. Pressure–flow charts provided by manufacturers are often based on tests performed using water, rarely blood. However, blood is a shear-thinning and viscoelastic fluid characterized by different flow properties than water. Methods: We performed a study evaluating pressure–flow curves during standardized conditions using human whole blood in two commonly available dual-lumen cannulae used in neonates, pediatric, and adult patients. Results were merged and compared with the manufacturer's corresponding curves obtained from the public domain. Results: The results showed that using blood as compared with water predominantly influenced drainage flow. A 10-80% higher pressure-drop was needed to obtain same drainage flow (hematocrit of 26%) compared with manufacturer's water charts in 13-31 Fr bi-caval dual-lumen cannulae. The same net difference was found in cavo-atrial cannulae (16-32 Fr), where a lower drainage pressure was required (Hct of 26%) compared with the manufacturer's test using blood with an Hct of 33%. Return pressure–flow data were similar, independent whether pumping blood or water, to the data reported by manufacturers. Conclusion: Non-standardized testing of pressure–flow properties of extracorporeal membrane oxygenation dual-lumen cannulae prevents an adequate prediction of pressure–flow results when these cannulae are used in patients. Properties of dual-lumen cannulae may vary between sizes within same cannula family, in particular concerning the drainage flow.